2014
DOI: 10.1007/s10162-014-0467-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Modulated Tones in Modulated Noise by Non-human Primates

Abstract: In natural environments, many sounds are amplitudemodulated. Amplitude modulation is thought to be a signal that aids auditory object formation. A previous study of the detection of signals in noise found that when tones or noise were amplitude-modulated, the noise was a less effective masker, and detection thresholds for tones in noise were lowered. These results suggest that the detection of modulated signals in modulated noise would be enhanced. This paper describes the results of experiments investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 69 publications
4
20
0
Order By: Relevance
“…However, the post-hoc tests showed that only the thresholds obtained with a 500 Hz tone were significantly higher than the others. This is consistent with higher audiometric thresholds for 500 Hz tones for macaques (see Bohlen et al 2014 for audiometric thresholds of monkeys C and D).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…However, the post-hoc tests showed that only the thresholds obtained with a 500 Hz tone were significantly higher than the others. This is consistent with higher audiometric thresholds for 500 Hz tones for macaques (see Bohlen et al 2014 for audiometric thresholds of monkeys C and D).…”
Section: Resultssupporting
confidence: 86%
“…This is consistent with a model of auditory detection previously developed (Bohlen et al, 2014), that implicates accumulation/integration, and it is generally consistent with models of sensory processing and sensorimotor integration (Vickers 1970; Usher and Mclelland 2001). Models of central neurons have also incorporated accumulation as an important aspect of computing decision (e.g., Wang 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Threshold shifts at 32 kHz are undefined because baseline thresholds ranged from 50-75 dB SPL and all post-exposure thresholds at this frequency exceeded the limit of the acoustic system (90 dB SPL). This frequency approaches the upper limits of audibility, where the audiogram steeply slopes in monkeys as young as 5-7 yrs, so high baseline thresholds at 32 kHz may not be pathological (Pfingst et al, 1978; Dylla et al 2013; Bohlen et al 2014). Note that ABR threshold shifts in the naïve macaque (M4 in Fig.…”
Section: Resultsmentioning
confidence: 89%